The Development of Student Worksheets in Writing Social Containing Explanation Texts in Class VI Studentsstate School 105345 Sidodadi - Diah Handayani Tarigan; Sutikno Sutikno; Rahmat Kartolo (Research Collaboration Community (RCC), 2021)
The problem in this study is how appropriate the teaching materials (Student Worksheet) in learning to write socially charged explanatory texts for class VI students are developed based on media experts, material experts, teachers and students?. The purpose of this study was to describe the feasibility of teaching materials (Student Worksheets) in learning to write socially charged explanatory texts for elementary/MI students. Class VI developed based on media experts, material experts, teachers and students. The research method used in this research is the research & development method. The research subject of this development product is the validator. The research subject of this development product is the validator. Assessment is done by filling out the validation sheet that has been provided, the validator in this study is the supervisor. In addition, the subjects of this research are sixth grade students of SD Negeri 105345 Sidodadi Ramunia, Beringin District. The object of this research is the Student Worksheet in learning to write socially charged explanatory texts in class VI SD Negeri 105345 Sidodadi Ramunia, Beringin District.